Answer:
We conclude that an equation in slope-intercept form for the line that passes through (-3,5) and is perpendicular to the graph of y+2x=4 will be:
![\:y=\frac{1}{2}x+\frac{13}{2}](https://tex.z-dn.net/?f=%5C%3Ay%3D%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B13%7D%7B2%7D)
Step-by-step explanation:
Given the line
y+2x=4
converting into the slope-intercept form y = mx+b where m is the slope
y = -2x+4
comparing with the slope-intercept form
Thus, the slope is: m = -2
We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:
slope = m = -2
The slope of the new line perpendicular to the given line = – 1/m
= -1/-2 = 1/2
Using the point-slope form
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
where m is the slope of the line and (x₁, y₁) is the point
substituting the values m = 1/2 and the point (-3, 5)
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y-5=\frac{1}{2}\left(x-\left(-3\right)\right)](https://tex.z-dn.net/?f=y-5%3D%5Cfrac%7B1%7D%7B2%7D%5Cleft%28x-%5Cleft%28-3%5Cright%29%5Cright%29)
![y-5=\frac{1}{2}\left(x+3\right)](https://tex.z-dn.net/?f=y-5%3D%5Cfrac%7B1%7D%7B2%7D%5Cleft%28x%2B3%5Cright%29)
Add 5 to both sides
![y-5+5=\frac{1}{2}\left(x+3\right)+5](https://tex.z-dn.net/?f=y-5%2B5%3D%5Cfrac%7B1%7D%7B2%7D%5Cleft%28x%2B3%5Cright%29%2B5)
![\:y=\frac{1}{2}x+\frac{13}{2}](https://tex.z-dn.net/?f=%5C%3Ay%3D%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B13%7D%7B2%7D)
Therefore, we conclude that an equation in slope-intercept form for the line that passes through (-3,5) and is perpendicular to the graph of y+2x=4 will be:
![\:y=\frac{1}{2}x+\frac{13}{2}](https://tex.z-dn.net/?f=%5C%3Ay%3D%5Cfrac%7B1%7D%7B2%7Dx%2B%5Cfrac%7B13%7D%7B2%7D)